Carbon Nanotube Effect on the Ductility, Flexural Strength, and Permeability of Concrete. (7th October 2019) - Mohsen, Mohamed O.; Al Ansari, Mohamed S.; Taha, Ramzi; Al Nuaimi, Nasser; Taqa, Ala Abu
Abstract : Recently, remarkable types of carbon nanofilaments called carbon nanotubes (CNTs) have raised the interest of many concrete and cementitious composite researchers due to their significant mechanical, electrical, thermal, kinetic, and chemical properties. These nanofilaments are considered promising applicants to use in producing high-performance cement-based composite materials. In this research, the effect of CNT use on the flexural strength, strain capacity, permeability, and microstructure of concrete was investigated. Concrete batches of 0, 0.03, 0.08, 0.15, and 0.25 wt.% CNTs were prepared using a mixing method that consisted of a 30-minute solution sonication and a 60-minute batch mixing. On the 28 th day, the mechanical properties were determined. The results indicated that concrete prepared using high CNT contents of 0.15 and 0.25 wt.% increased the flexural strength by more than 100% in comparison with 0% CNT concrete. Furthermore, the results showed that CNTs would increase the ductility of concrete beams by about 150%. The permeability test results showed the benefits of CNT inclusion in reducing the permeability of concrete. The permeability coefficient (kT) decreased by at least 45% when CNTs were added to concrete. A qualitative microstructural analysis illustrated the uniform dispersion of CNT filaments within the concrete hydration products in all batches.